Of saints, sows or smiths? Copper-brazed iron handbells in Early Medieval England. Issue 1 (2nd January 2020) - Willmott, Hugh; Daubney, Adam
ABSTRACT: Copper-brazed iron handbells were a distinctive feature of monastic life in Early Medieval Ireland, Scotland and Wales. Handbells were used in liturgy, prayer, worship, and later as reliquaries. In England, brazed bells of the seventh to ninth centuries take on a greater range of sizes and forms and are found on a wider variety of sites. As a consequence, their roles within Christianity have been questioned, and associations with animals and itinerant smiths have been emphasised instead. Recent archaeological investigation of an Anglo-Saxon marsh-island at Little Carlton, Lincolnshire has resulted in one of the largest assemblages of copper-brazed iron bells from any site in England, comparable to similar collections from Flixborough and Brandon. Taking into consideration the inclusion of brazen bells in some ritualistic 'closure hoards', this paper argues that whilst Anglo-Saxon plain iron bells may have fulfilled a range of profane functions, those that were copper-brazed, regardless of their size, were important objects amongst early Christian communities in England, and the Northumbrian church in particular.